Is It Not The Right Time To Consider Trivalent Mumps Vaccine (MMR) In The National Immunization Programme of Nepal? If Not Now, Then When? - Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2023)
Vaccination is the process of administration of a vaccine to help the immune system develop immunity from a disease resulting in reduction of child mortality, morbidity and disability in vaccine preventable diseases. Nepal started its pilot vaccination program in 1979 (2034 B.S) and after a decade (1989), the Expanded Program on Immunization (EPI) was followed to the whole country with the aim of universal vaccination in children. National immunization programme (NIP) provides vaccination services free of cost to the children living in marginalized communities and geographical regions difﬁcult to reach through outreach sessions. Although many more vaccines have been added to the NIP of Nepal since then, vaccination against mumps is still missing. Nepalese children are being vaccinated with MR vaccine (measles and rubella) at 9 completed months and a booster at 15 months in spite of MMR (measles, mumps and rubella) vaccine. The time to re-think and consider mumps vaccine (MMR) in the immunization schedule of Nepal by the government of Nepal has arrived now. Including MMR vaccine in the national immunization schedule would ultimately result in the reduction of the outbreaks and associated morbidity that occur annually along with the economic beneﬁts.